MENINGKATKAN KEDISIPLINAN KERJA DI BIDANG CONTENT CREATOR - Yayu Lutfiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2025)
Work discipline is obedience to all provisions in the organization, both written and in the form of mere promises, that without such obedience, all the goals of the organization will not be achieved. This article aims to improve work discipline in the field of content creators. The research method used in this article is a qualitative descriptive research method with data collection techniques in the form of spoken or written words about observable human behavior. The results of this study indicate that in improving work discipline in the field of content creators, there still needs to be an increase for employees in the content creator division from research conducted by researchers. This study aims to determine how much influence Work Discipline has on Content Creator PT. Pojok Satu Indonesia.